Intellectual Footwear and Disinfectant Bucket - Begmatov Khurshid Esonalievich (Genius Journals, 2024)
In the article human beings needs come without one how many to amenities have bolga , disinfectant , foot temperature normalizing, in the leg unconscious smells lubricat , dust , oil and water impermeable modern nanotechnologies based on created smart leg clothes about info given
Keywords: Infection; Temperature; Nanotechnology